Relationship Between Employees’ Perfectionism and Workaholism: The Role of Dedication-to-Work Promoting Organization - Morkevičiūtė, Modesta; Endriulaitienė, Auksė (Socialiniai tyrimai, 2022)
The aim of the present study was to investigate the moderating role of perceived dedication-to-work promoting organization for the relationship between employees’ perfectionism and workaholism. A total of 964 employees (514 females and 450 males) working in different Lithuanian organizations participated in the cross-sectional study. Data were collected by means of online self-administered questionnaires. Workaholism was measured using DUWAS-10 proposed by Schaufeli et al. (2009). To measure perfectionism, a short version of the Multidimensional Perfectionism Scale (MPS; Hewitt and Flett, 1991) was used. A questionnaire proposed by Allen (2001) was used to assess the perceptions of whether an organization encourages employees to focus solely on work or whether it supports their family responsibilities as well. It was hypothesized that the positive relationship between perfectionism and workaholism was stronger for employees working in dedication-to-work promoting organizations. The assumption was confirmed. It was obtained that the risk of workaholism was higher for employees having high levels of perfectionism and perceiving organization as promoting dedication to work.